Work-related Musculoskeletal Disorders among mail sorting officers in Sri Lanka: a cross sectional study - Warnakulasuriya, S. S. P.; Peiris-John, R.; Sivayogan, S.; Sathiakumar, N.; Coggan, D.; Wickremasinghe, A. R. (My University, 2012)
Background: Mail sorting requires repetitive movements of the upper limbs, target oriented tasks, long term standing or sitting, concentration and a good memory. The extent of musculoskeletal disorders (MSDs) among mail sorting officers (MSOs) is not known. This study was conducted to determine the prevalence and associated factors with work-related MSDs among MSOs in Sri Lanka. Methods: 250 randomly selected MSOs who were attached to the Central Mail Exchange, Colombo, were administered a pre-tested questionnaire after obtaining informed written consent. Information on demographic characteristics, musculoskeletal symptoms of the different body parts, job tasks, work history, job satisfaction, sick leave, feelings of job security, and personal perceptions of musculoskeletal symptoms during the past month were obtained. Data were analyzed using SPSS (version 16). Descriptive analyses were used to describe variables and chi-square tests were used to determine associations between pain symptoms and associated variables. Results: The prevalence of backache was highest (38.4%), followed by shoulder pain (27.6%), knee pain (21.2%), neck pain (16.4%), wrist and arm pain (11.2%) and elbow pain (10%). 59.6% of MSOs had experienced at least one MSDs sometime during the past 12 months. Mail sorting activities involved repetitive hand and wrist movements for more than four hours a day (n=239), repetitive bending and straightening of elbow more than one hour a day (n=239), keeping the hand above shoulder height for more than one hour a day (n=239) and climbing up and down more than 30 steps (n=218) a day. Height was significantly associated with shoulder pain (OR=1.056, 95%CI=1.069-3.577). Pain in all of the other sites was not associated with known risk factors in other studies. Conclusion: The predominant ergonomic problem in mail sorters in Sri Lanka are in the lower back, shoulder and neck areas. Although there is a high prevalence of some musculoskeletal symptoms in MSOs, most of the known risk factors identified in other studies such as age, right or left handedness, years of experience in current job, smoking habit and job satisfaction etc., were not significantly associated with MSDs in this population. Other physical, psychosocial and environmental factors need to be investigated.
Keywords: Musculoskeletal disorders; Mail sorting officers